2015
DOI: 10.1186/s12936-015-0729-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a multi-well colorimetric assay to determine haem species in Plasmodium falciparum in the presence of anti-malarials

Abstract: BackgroundThe activity of several well-known anti-malarials, including chloroquine (CQ), is attributed to their ability to inhibit the formation of haemozoin (Hz) in the malaria parasite. The formation of inert Hz, or malaria pigment, from toxic haem acquired from the host red blood cell of the parasite during haemoglobin digestion represents a pathway essential for parasite survival. Inhibition of this critical pathway therefore remains a desirable target for novel anti-malarials. A recent publication describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 25 publications
6
91
1
1
Order By: Relevance
“…Interestingly, for each line, the free heme concentration curve crossed the parasite growth curve at approximately the same mid-point (IC 50 value), indicating that the inverse relationship between CQ action on free heme levels and growth inhibition that was previously observed for parasite lines encoding wild-type pfcrt [73] is preserved among lines encoding CQ-resistant pfcrt alleles. These data provide compelling evidence that for both resistant and sensitive parasites, CQ-mediated growth inhibition results primarily from this drug’s inhibition of Hz formation, which the parasite uses to detoxify reactive free heme.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, for each line, the free heme concentration curve crossed the parasite growth curve at approximately the same mid-point (IC 50 value), indicating that the inverse relationship between CQ action on free heme levels and growth inhibition that was previously observed for parasite lines encoding wild-type pfcrt [73] is preserved among lines encoding CQ-resistant pfcrt alleles. These data provide compelling evidence that for both resistant and sensitive parasites, CQ-mediated growth inhibition results primarily from this drug’s inhibition of Hz formation, which the parasite uses to detoxify reactive free heme.…”
Section: Resultssupporting
confidence: 52%
“…In a dose-dependent manner, CQ causes an increase in toxic free heme, a decrease in the formation of chemically inert Hz crystals, and an accompanying reduction in parasite survival [32]. To date, the profiles of heme fractions have only been explored in CQ-sensitive (D10, NF54 and D6) parasites [72,73]. Given the central role of pfcrt in dictating parasite responses to CQ, we examined the composition of heme species in CQ-treated and untreated isogenic parasites encoding either the CQ-sensitive (wild-type) pfcrt allele GC03 or the CQ-resistant (mutant) pfcrt alleles Cam734 or Dd2.…”
Section: Resultsmentioning
confidence: 99%
“…The significant changes in free heme and Hz levels for these benzamides suggested that the precise manner by which they cause heme-related toxicity differs from that of CQ, since much smaller changes in free heme and Hz levels by ~5 fg/cell and ~15 fg/cell respectively were observed at 2.5 times the CQ IC 50 . 26 Other quinoline antimalarials, such as AQ, QN and mefloquine showed even smaller changes than CQ. 7 This finding demonstrates that higher levels of free heme are required for disrupting parasite growth in the case of the benzamides compared to CQ and other quinoline antimalarials.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, several compounds, representing two of the primary scaffolds, caused extraordinarily high levels of free heme at 2.5 times the relevant IC 50 (30–50%) compared to the levels seen with CQ and other quinoline-containing scaffolds (8–14%). 7, 26 Two of these compounds contained either a pyridylbenzamide or phenylbenzamide moiety. The benzamide chemotype was found to occur 33 times among the βH hits, with 13 compounds displaying parasite growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Three compounds caused extraordinarily high levels of non-Hz free heme (30−50% of total heme) at 2.5 times their respective IC 50 when compared to those seen with CQ and other quinoline-containing scaffolds (8−14%). 17,18 Two of these compounds were benzamides, reported elsewhere, 19 and the other, a triarylimidazole, which attained a free heme content of 43%. The triarylimidazole class also displayed a high hit rate for parasite activity, as six of seven βH inhibitors were active against P. falciparum (Table 1).…”
mentioning
confidence: 99%